2009
DOI: 10.3758/mc.37.7.1040
|View full text |Cite
|
Sign up to set email alerts
|

Verbal representation in task order control: An examination with transition and task cues in random task switching

Abstract: Recent task-switching studies in which a predictable task sequence has been used have indicated that verbal representation contributes to the control of task order information. The present study focused on the role of verbal representation in sequential task decisions, which are an important part of task order control, and examined the effects of articulatory suppression in a random-task-cuing paradigm with two different types of cues presented just before the presentation of a stimulus: a transition cue and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
4
23
0
Order By: Relevance
“…On the one hand, it has been shown that the requirement to verbalise the task goals enhances task switching performance (e.g., Goschke, 2000). On the other hand, taxing verbal working memory, in particular the phonological loop in Baddeley's model, makes task switching more error prone and slower (Baddeley, Chincotta, & Adlam, 2001;Bryck & Mayr, 2005;Emerson & Miyake, 2003;Liefooghe, Vandierendonck, Muyllaert, Verbruggen, & Vanneste, 2005;Miyake, Emerson, Padilla, & Ahn, 2004;Saeki & Saito, 2004a;Saeki & Saito, 2004b;Saeki & Saito, 2009;Saeki, Saito, & Kawaguchi, 2006). These findings support the hypothesis that maintaining a verbal representation of the task goal in working memory helps to keep attention focused on the task at hand.…”
Section: Working Memory and Task Switchingsupporting
confidence: 60%
“…On the one hand, it has been shown that the requirement to verbalise the task goals enhances task switching performance (e.g., Goschke, 2000). On the other hand, taxing verbal working memory, in particular the phonological loop in Baddeley's model, makes task switching more error prone and slower (Baddeley, Chincotta, & Adlam, 2001;Bryck & Mayr, 2005;Emerson & Miyake, 2003;Liefooghe, Vandierendonck, Muyllaert, Verbruggen, & Vanneste, 2005;Miyake, Emerson, Padilla, & Ahn, 2004;Saeki & Saito, 2004a;Saeki & Saito, 2004b;Saeki & Saito, 2009;Saeki, Saito, & Kawaguchi, 2006). These findings support the hypothesis that maintaining a verbal representation of the task goal in working memory helps to keep attention focused on the task at hand.…”
Section: Working Memory and Task Switchingsupporting
confidence: 60%
“…This proposal is also consistent with the findings reported by Bryck and Mayr (2005) which suggest that verbalization of sequential information in task switching is critical for maintenance of sequential courses of actions or sequential plans. These and other studies (Baddeley, Chincotta, & Adlam, 2001;Emerson & Miyake, 2003;Miyake, Emerson, Padilla, & Ahn, 2004;Saeki & Saito, 2009) strongly indicate that working memory forms a basis for task switching without implying that shortage of working memory capacity would completely disrupt task-switching performance.…”
Section: Modeling Assumptionsmentioning
confidence: 54%
“…This extends the results of earlier studies, concerned with rapid switching, to our more long- To explain our results, comparison of the demands placed on switching in the two different paradigms may be helpful. In rapid task switching, negative effects of suppression have been observed when trial-to-trial uncertainty is high (Saeki & Saito, 2009). Thus, the problem appears to be how participants keep track of where they are in a sequence of alternating tasks, a process that is probably facilitated by the subvocalization of appropriate cues (e.g., "plus, minus, plus .…”
Section: The Role Of the Phonological Loop In Action Controlmentioning
confidence: 99%